2014
DOI: 10.4103/0974-620x.127910
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomographic assessment of retinal nerve fiber layer thickness changes before and after glaucoma filtration surgery

Abstract: Background: Glaucomatous Optic Neuropathy (GON) is very common in the glaucoma patients, and impaired effect of glaucoma is measured by the Retinal Nerve Fiber Layer (RNFL) thickness.Objective: The study was conducted to find out the mean RNFL thickness, RNFL thickness in different quadrants, Intra-Ocular Pressure (IOP) changes, and visual field changes after filtration surgery in different ages and genders using Optical Coherence Tomography (OCT).Materials and Methods:The study was an interventional case-seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The mean preoperative IOPs reported by Sarkar et al . 15 and Rebolleda et al . 17 were 26.9 ± 6.4 mmHg and 23.6 ± 5.1 mmHg, respectively.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The mean preoperative IOPs reported by Sarkar et al . 15 and Rebolleda et al . 17 were 26.9 ± 6.4 mmHg and 23.6 ± 5.1 mmHg, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…It is therefore possible that the amount of RNFL thinning measured in the present study (5.4 µm) was not detected in the previous study. Second, the preoperative IOPs of the enrolled patients differed 10,1315,17 . In subgroup analyses based on preoperative peak IOPs, there was significant RNFL thinning, and the higher the preoperative peak IOP, the greater the postoperative RNFL thinning in patients with a preoperative peak IOP ≥ 37 mmHg (median value).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conflicting results have been reported regarding improvement in the postoperative RNFL thickness. Several studies have reported a significant change in RNFL thickness following IOP reduction (Aydin et al, 2003;Sarkar et al, 2014). Similarly, the study of Chang et al found a significant increase in RNFL, but with no correlation with IOP (Chang et al, 2007).…”
Section: Discussionmentioning
confidence: 91%
“…In practice and clinical trials, reduction of intraocular pressure by a surgical method has been shown to affect the rate of progression of glaucoma(Bertrand et al, 2014). Surgical treatment may improve structural(Sarkar et al, 2014;Irak et al, 1996) and functional parameters of the eye(Bertrand et al, 2014).…”
mentioning
confidence: 99%